Effects of human head hair on performance and thermoregulatory responses during 10-km outdoor running in healthy men - Angelo Ruediger Pisani Martini; João Batista Ferreira-Júnior; Daniel Barbosa Coelho; Diego Alcântara Borba; Leonardo Gomes Martins Coelho; Luciano Sales Prado (Universidade Federal de Santa Catarina, 2016)
The aim of the present study was to evaluate the effects of human head hair on performance and thermoregulatory responses during 10-km outdoor running in healthy men. Twelve healthy males (29.5 ± 3.7 years, 174.9 ± 4.3 cm, 72.7 ± 3.2 kg and VO2max 44.6 ± 3.4 ml.kg-1.min-1) participated in two self-paced outdoor 10-km running trials separated by 7 days: 1) HAIR, subjects ran with their natural head hair; 2) NOHAIR, subjects ran after their hair had been totally shaved. Average running velocity was calculated from each 2-km running time. Rectal temperature, heart rate and physiological strain index were measured before and after the 10-km runs and at the end of each 2 km. The rate of heat storage was measured every 2 km. The environmental stress (WBGT) was measured every 10 min. The running velocity (10.9 ± 1 and 10.9 ± 1.1 km.h-1), heart rate (183 ± 10 and 180 ± 12 bpm), rectal temperature (38.82 ± 0.29 and 38.81 ± 0.49oC), physiological strain index (9 ± 1 and 9 ± 1), or heat storage rate (71.9 ± 64.1 and 80.7 ± 56.7 W.m-1) did not differ between the HAIR and NOHAIR conditions, respectively (p>0.05). There was no difference in WBGT between the HAIR and NOHAIR conditions (24.0 ± 1.4 and 23.2 ± 1.5ºC, respectively; p=0.10). The results suggest that shaved head hair does not alter running velocity or thermoregulatory responses during 10-km running under the sun.